Bats Disease-Prone but Beneficial - Mikkola, Heimo (IntechOpen, 2022)
Bats are widely distributed and vary enormously in their ecology, sociality, and behavior. They offer diverse cultural and economic contributions to human populations, such as ecotourism, guano, medicinal products, religious significance, and vector control, to name a few. Insectivorous bats consume massive quantities of insects and other arthropods, controlling important agricultural pests and potential disease vectors. Bats feeding on nectar help to maintain diversity in forests through the dispersal of seeds and pollen, essential to many plant species with high economic, biological, and cultural value. At the same time, bats are often associated with zoonotic disease risks, a trend that has been magnified by the global COVID-19 pandemic, although no direct infection from bat to human has been demonstrated. Rapid deforestation is also a major contributing factor to new viral emergences. This book suggests that education is a suitable tool to minimize prejudice against bats and a key step to creating a harmonious coexistence between humans and bats. Chapters address such topics as bats in folklore and culture, bat dispersal patterns, bats in ecosystem management, pesticide exposure risks, roost-tier preference, diversity and conservation, and ecology of white-nose syndrome.